Dexamethasone induced Dectin-1 activation enhances NLRP3 inflammasome activation - Koerber, Ruth-Miriam; Oberbeck, Sebastian; Kotthoff, Philipp; Daecke, Solveig N.; Brossart, Peter; Held, Stefanie A. E. (Frontiers in Immunology, 2025)
Systemic candidiasis is a serious complication in immunocompromised patients, with Candida albicans emerging as the most common opportunistic pathogen. In various therapeutic treatment regimens the immunosuppressive agent Dexamethasone is used. Dexamethasone itself impairs the function of dendritic cells and reduces thereby their capacity for T-cell proliferation through the activation of Dectin-1 by β-glucans. In the present study, we reveal that these tolerogenic dendritic cells (Dex-DCs) have an increased secretion of IL-1ß and IL-18 when stimulated with β-glucans. We show an increased formation of ASC specks, which are crucial for recruiting pro-caspase-1, indicating an elevated inflammasomal activity. In line with this, we were able to show that treatment of tolerogenic dendritic cells with a NLRP3 inhibitor prior to Dectin-1 stimulation normalized the secretion of IL-1ß and IL-18. Furthermore, the addition of Caspase- and Syk-inhibitors led to diminished inflammasome activation as well as to less pyroptosis and apoptosis in response to β -glucan stimulation. Finally, we identified elevated production of reactive oxygen species (ROS) upon β-glucan stimulation in DexDCs as a possible mechanism for apoptosis induction as it can be reversed by the treatment with a specific anti-Dectin-1 antibody. Moreover, the underlying mechanism of the NLRP3 activation seems to be mediated through mitochondrial DNA release induced by mitochondrial ROS. Taken together, the present study demonstrates that Dectin-1 stimulation of tolerogenic DCs can result in severe pro-inflammatory responses due to cytokine release and subsequent NLRP3 inflammasome activation. In conclusion, the application of NLRP3 inflammasome inhibitors to patients treated with corticosteroids like Dexamethasone may significantly improve their outcome as they might be well-protected against local or severe systemic fungal infections.